The collaborative dream: the life cycle of knowledge co-production projects and the survival dilemma - Belen Pedregal; Pamela E. Degele (Ecology and Society)
In this paper we present and critically evaluate a participatory mapping project called the Map of Water Conflicts in Andalusia (Spain) led by researchers at the University of Seville from 2017 to 2019. According to the available literature, projects of this nature denote initial enthusiasm, followed by decline and abandonment within a period of approximately five years. At the crossroads of the Map’s disappearance, we critically analyze the project expectations and outcomes while addressing the challenges of sustaining co-production interest and validity over time.